Benefits, barriers and guideline recommendations for the implementation of serious games in education for stakeholders and policymakers. (24th October 2014) - Tsekleves, Emmanuel; Cosmas, John; Aggoun, Amar
Abstract: Serious games and game‐based learning have received increased attention in recent years as an adjunct to teaching and learning material. This has been well echoed in the literature with numerous articles on the use of games and game theory in education. Despite this, no policy for the incorporation of serious games in education exists to date. This review paper draws from the literature to provide guideline recommendations that would help educators and policymakers in making the first step towards this.